Pseudoxanthomatous Salpingitis: A Rare Granulomatous Pathology of the Fallopian Tube - Asha R. Rao; Damodar R. Rao; Yingngam Wangnaolim; Padmashri Giridharan (Journal of Human Reproductive Sciences, 2024)
Uncommon presentations of granulomatous salpingitis are pseudoxanthoma salpingitis (PSX) and xanthogranulomatous salpingitis (XGS). The clinical features and image modalities can mimic ovarian malignancy. Thus, a proper pre-operative evaluation of this entity is vital to avoid radical treatment. Here, we report a case of a 31-year-old woman with primary infertility diagnosed with pseudoxanthoma salpinx. This patient was a known case of endometriosis and presented with gross ascites.